2020
DOI: 10.15562/ism.v11i2.667
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi sarkopenia dan frailty di desa Pedawe, Mangupura, Serai dan Songan

Abstract: Background: Frailty is characterized by a decrease in multi-organ physiological functions. Sarcopenia and frailty have a significant impact on individuals and society so it is necessary to know the prevalence in the community. This study aimed to determine the prevalence of sarcopenia and frailty in rural areasMethod: The was a cross-sectional study in the elderly population in the villages of Pedawa, Mangupura, Serai and Songan. Measurement of muscle mass using bioelectrical impedance analysis (BIA) and categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As sarcopenia impairs the QoL significantly, [12][13][14][15][16][17][18] this disease-specific instrument may provide a better assessment of the patient's condition and disease progression. As Indonesia has an increasing number of elderly population, 6,7 many of whom may have sarcopenia based on the current prevalence, [8][9][10] the need for a sarcopenia-specific evaluation tool is necessary. This study was conducted to provide a valid and reliable QoL assessment instrument for the Indonesian elderly with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As sarcopenia impairs the QoL significantly, [12][13][14][15][16][17][18] this disease-specific instrument may provide a better assessment of the patient's condition and disease progression. As Indonesia has an increasing number of elderly population, 6,7 many of whom may have sarcopenia based on the current prevalence, [8][9][10] the need for a sarcopenia-specific evaluation tool is necessary. This study was conducted to provide a valid and reliable QoL assessment instrument for the Indonesian elderly with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this number is expected to rise each year until the elderly make up 19.8% of the Indonesian population in 2045. 6,7 According to several studies, [8][9][10] the prevalence of sarcopenia in Indonesia ranges from 9.1% to 53.0%, with the prevalence of frailty ranging from 17.0% to 36.7%.…”
mentioning
confidence: 99%
“…4 Based on the research which conducted Putra et al, which involved 235 people in rural Bali, the prevalence of sarcopenia was 58.7%, increasing with age. 5 Vitamin D deficiency is a common health problem worldwide. Hirani et al, reported that low serum 1,25(OH)2D3 and low 25(OH)D independently associated with the incidence of sarcopenia over the next 5 years.…”
Section: Introductionmentioning
confidence: 99%